The Impact of Virtual Interviews on the Geographic Distribution of Ophthalmology Match Results in the 2020–2021 Cycle - Rasendran, Chandruganesh; Rahman, Sarah; Younis, Uthman; Wadhwa, Raoul; Kapadia, Manasvee; Lass, Jonathan H.; Ohsie-Bajor, Linda H. (Journal of Academic Ophthalmology, 2021)
Background Instead of the traditional in-person interviews, the 2020 to 2021 ophthalmology application cycle was conducted with virtual interviews due to coronavirus disease 2019 (COVID-2019). Little is known about differences between the results of this application cycle with previous years.Objectives The aim of this study was to determine the effect of virtual interviews on the geographic distribution of matched ophthalmology residency applicants.Methods Information was collected on the medical school location and matched residency program location for 2020 to 2021 applicants as well as applicants during the 2016 to 2017, 2017 to 2018, and 2018 to 2019 cycles from publicly available Web sites. Pearson chi-squared tests were conducted to determine whether there was a significant difference in the proportion of applicants matching in the same region, state, and institution as their medical schools in the 2020 to 2021 interview cycle when compared with past cycles.Results Three-hundred seventy-five applicants from 2020 to 2021 and 1,190 applicants from 2016 to 2019 application cycles were analyzed. There was no difference in the type of medical school attended (allopathic vs. osteopathic vs. international medical graduate) (p = 0.069), the likelihood of attending a residency program in the same region as the home medical school (54% for 2020–2021 vs. 57% for 2016–2019 applicants, p = 0.3), and the likelihood of attending a residency program in the same state as the home medical school (31 vs. 28%, p = 0.2). There was a higher likelihood of applicants during the 2020 to 2021 cycle matching at a residency program affiliated with their home medical school than previous cycles (23 vs. 18%, p = 0.03).Conclusions Virtual interviews did not increase the likelihood of medical students staying in the same region or state as their medical school, while there was a higher likelihood of applicants matching at residency programs at institutions affiliated with their medical schools. A hybrid approach to maintain geographic diversity of applicants' final residency programs involving virtual interviews with the addition of in-person away rotations is suggested.
Keywords: virtual interviews; COVID-19; visiting student; applicants; ophthalmology residency